2022
DOI: 10.3390/su15010272
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Bankruptcy Risk in the Hotel Industry as a Condition of the COVID-19 Crisis Using Time-Delay Neural Networks

Abstract: In this paper we demonstrate a new conceptual framework in the application of multilayer perceptron (MLP) artificial neural networks (ANNs) to bankruptcy risk prediction using different time-delay neural network (TDNN) models to assess Altman’s EM Z“-score risk zones of firms for a sample of 100 companies operating in the hotel industry in the Republic of Serbia. Hence, the accuracies of 9580 forecasting ANNs trained for the period 2016 to 2021 are analyzed, and the impact of various input parameters of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…As another aim is to keep works that provide clear-cut hotel results, studies using broader tourism or hospitality firm samples inseparably and in an indistinguishable manner are not included (Abidin et al 2020(Abidin et al , 2021Barreda et al 2017;Laguillo et al 2019;Li et al 2017Li et al , 2019Park and Hancer 2012;Pisula 2020). Another sub-filter regarding study relevance is the exclusion of ex ante bankruptcy risk assessments that do not deal with actual bankruptcies or a measure of financial distress, where the aim is to project a future potential credit profile for hotels (Gallo et al 2018;Matejić et al 2022;Špiler et al 2022;Vivel-Búa et al 2018). Studies dealing explicitly with the going concern issue (Fernández et al 2018;Zhai et al 2015) and a recent study where the only financial metric, the initial injected capital, which can be considered a balance sheet item, was not promoted in the final model (Yuan et al 2023), are excluded too.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As another aim is to keep works that provide clear-cut hotel results, studies using broader tourism or hospitality firm samples inseparably and in an indistinguishable manner are not included (Abidin et al 2020(Abidin et al , 2021Barreda et al 2017;Laguillo et al 2019;Li et al 2017Li et al , 2019Park and Hancer 2012;Pisula 2020). Another sub-filter regarding study relevance is the exclusion of ex ante bankruptcy risk assessments that do not deal with actual bankruptcies or a measure of financial distress, where the aim is to project a future potential credit profile for hotels (Gallo et al 2018;Matejić et al 2022;Špiler et al 2022;Vivel-Búa et al 2018). Studies dealing explicitly with the going concern issue (Fernández et al 2018;Zhai et al 2015) and a recent study where the only financial metric, the initial injected capital, which can be considered a balance sheet item, was not promoted in the final model (Yuan et al 2023), are excluded too.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of failures, many studies have reported high percentages of firm failures in the hospitality industry in various countries (Abidin et al 2020;Boer 1992;Chathoth et al 2006;Pisula 2020;Situm 2023;Solnet et al 2010;Westgaard and van der Wijst 2001). An increased bankruptcy risk for the hotel sector may arise after the end of the COVID-19 period, as projected recently in a few studies (Crespí-Cladera et al 2021;Matejić et al 2022;Špiler et al 2022), as also due to the current energy and cost of living crises.…”
Section: Firm Failures In the Hotel Industry: Motivation For Sectoral...mentioning
confidence: 99%
“…According to Shetty et al [17], the 1990s ushered in a new phase in the evolution of business failure prediction models, introducing innovative methods, particularly artificial intelligence algorithms, including neural networks (Špiler et al [41]) and decision trees. These artificial intelligence-based techniques offer promising alternatives to traditional statistical models, addressing their principal shortcomings (Dong and Chen [42]).…”
Section: Financial Distress Prediction Modelsmentioning
confidence: 99%